Penerapan Model Pembelajaran Langsung pada Kompetensi Dasar Massage Wajah di SMK Negeri 6 Surabaya: Prosedur Penerapan Model Pembelajaran Langsung pada Kompetensi Dasar Massage Wajah untuk Meningkatkan Kemampuan Kognitif dan Psikomotor. - Sekar Arum, Putri Lia (Jurnal Tata Rias, 2021)
Beauty Industry in Indonesia develops so fast so Vocational schools, especially having the beauty departments, have to be able to run after by training their students. One of adorable skills is Face Massage. These schools, therefor eagerly have an effort in improving their students output. Direct Instruction is an answer of the need of the Beauty Industry in which this technique is going to build the professional skill of students. This research aims to know the achievement of the syntax of Direct Instruction, improving of Cognitive and Psychomotor output result, students’ activities and responses along the progress. The kind of this research is pre-experimental design. Research Plan uses one group pre and post-test design. The subject of the research is 30 students of X Grade Tata Kecantikan of State Vocational School 6 of Surabaya. The collecting data uses observation method, Knowledge and Skill Test and Questionnaire. The result of the research shows that the achievement of the syntax, activities and responses of students, generally categorised as Good Grade. The output of students’ study shows an improvement. T-Test also shows that the improvement of the Face Massage achievement. Hereby, it can conclude that the direct instruction to Basic Competency of Face Massage can improve the result of the students’ study of X grade Tata Kecantikan of State Vocational School 6 of Surabaya.